The Analysis of SWOT Management in Pra Pelatnas Training Center of Persatuan Atletik Seluruh Indonesia (PASI), East Java - Selvy Cahya Wulandari; Amrozi Khamidi; Gigih Siantoro (BIRCU, 2020)
In the science of sports management, it is explained that the optimal performance of an athlete is inseparable from the application of management functions in the sports organization. The participates in. PASI Pengprov East Java as the organizer of the Pre Pelatnas Training Center should have good management so that all activities run smoothly and succeed in achieving their goals to identify the readiness level of each management function. Training Center Pra Pelatnas PASI East Java Pengprov in an effort to achieve its goals, it is necessary to do an analysis. A fairly good method for analyzing management functions is SWOT analysis. This study is focused on analyzing and identifying the strengths, weaknesses, opportunities and threats in each management function, namely, Planning (organizing), implementation (actuating), evaluation (controlling). The implementation of Training Center Pra Pelatnas PASI East Java Pengprov. This type of research is a qualitative research with a descriptive method approach. Sources of research data come from observations, interviews with administrators, coaches and athletes and documents. The data obtained will be analyzed using triangulation techniques, namely data validation by checking the facts obtained from different data sources. The results of the SWOT analysis on management generally conclude that the management process Training Center It can be said that the Pre Pelatnas for the Indonesian Athletics Association (PASI) East Java Provincial Government has been carried out quite effectively in all management functions, namely Planning, Organizing, Actuating, and Controlling and has achieved good and appropriate results. However, improvements and proper strategies are still needed to minimize existing weaknesses and overcome threats.